Keefektifan Metode Klarifikasi Nilai untuk Meningkatkan Kesadaran Nilai Tanggung Jawab Akademik pada Siswa - Royen Dyanasta (Universitas Ahmad Dahlan, 2015)
This study aims to determine the effectiveness of value clarification techniques in raising the elementary school students’ awareness towards the value of the academic responsibilities. This is an experimental studies in which one group possesed in pretestt-posttest design. There were eight participants of elementary school students. They were selected through purposive sampling techniques. The instrument used for collecting the data was the scale of awareness towards the value of the academic responsibilities for elementary school students. The data were analyzed using the nonparametric statistical test of Wilcoxon sign rank test. The results of the analysis showed that there is a different value (z) -2.524 in a significant degree of < 0.05. The pretest results showed that the average score of the elementary school students’ awareness towards the value of the academic responsibilities was 66, on the other hand, the posttest results showed that the average score was 94,5. Based on this study, it can be concluded that value clarification techniques is effective in raising the elementary school students’ awareness towards the value of the academic responsibilities. The is study can be used as the consideration for counseling teachers in providing a wide range of guidance and counseling services especially on the developing the students’ value of the academic responsibilities through value clarification techniques.